THE EFFORT TO REPAIR TODDLER’S NUTRITION DUE TO LACK OF VITAMIN A - Andriyani, Fatika (Journal of Ultimate Public Health, 2017)
Lack of Vitamin A (KVA) is still a widespread problem throughout the world, especially in developing countries and can occur at any age, especially during growth. KVA in the body can cause various types of diseases that are